Decarburization of TiC in Ni activated sintered W–xTiC (x=0, 5, 10, 15 wt%) composites and the effects of heat treatment on the microstructural and physical properties - Genc, A.; Coskun, S.; Ovecoglu, M. L. (Elsevier BV, 2010)
Abstract Blended elemental W– x TiC ( x  = 0, 5, 10, 15 wt%) powders were mechanically alloyed (MA’d) for 30 h in a SPEX Mixer/Mill at room temperature. About 1 wt% Ni was added to each MA’d batch as sintering aid which were further milled for 1 h. MA’d powders were sintered at 1400 °C for 2 h under Ar, H 2 gas flowing conditions and annealed at 1600 °C for 6 h under Ar atmosphere. Microstructural characterizations of as-sintered and annealed samples were conducted using XRD and SEM. XRD patterns of the as-sintered and annealed samples revealed the presence of the matrix W and Ni phases, whereas (Ti x ,W 1− x ) solid solution phase came into existence after annealing. In addition to XRD patterns, hot combustion and infrared detection measurements revealed the decarburization of TiC. Relative density values varied between 85.2% and 96.4% after sintering. The density values of sintered samples decreased with increasing TiC content. After annealing, a maximum relative density value of 99.8% was achieved. Vickers microhardness values varied between 5.11 GPa and 10.79 GPa for as-sintered samples and a maximum microhardness value of 8.1 GPa was measured after annealing. Wear resistance of the as-sintered samples increased with increasing TiC content.